Metabolomic analysis suggests thiamine monophosphate as a potential marker for mesenchymal stem cell transplantation outcomes in patients with SLE - Bin Yang; Xuebing Feng; Lingyun Sun; Xiaojun Tang; Xiaoman Jiang; Zhuoyang Jia (Lupus Science and Medicine)
Objective The objective of this research is to identify metabolic markers associated with successful treatment by evaluating the effect of mesenchymal stem cell transplantation (MSCT) on the metabolic profiles of patients with SLE.Methods Plasma samples were collected from 20 patients with SLE before and after MSCT. Principal component analysis (PCA) was used to distinguish pretreatment and post-treatment groups and pathway analysis for identifying involved metabolic pathways. Clinical variables were monitored with a median follow-up time of 180 days. Pearson correlation and receiver operating characteristics (ROC) analysis were employed to associate metabolite changes with clinical outcomes and to predict treatment success.Results We detected 18 121 metabolites, with 1152 showing significant changes post-treatment, which could be clearly distinguished between pretreatment and post-treatment groups through PCA. Pathway analysis indicated involvement in riboflavin and thiamine metabolism. Clinical improvements were observed at a median follow-up time of 180 days after MSCT, including decreased SLE Disease Activity Index scores, urine protein/creatinine ratios, and erythrocyte sedimentation rates, along with increased levels of complement C3 and C4, haemoglobin, and platelets. Pearson correlation indicated that specific metabolite changes were associated with clinical improvements, particularly increases in thiamine monophosphate (TMP) and asiaticoside levels. ROC analysis identified TMP level changes as the most predictive of treatment success, with a 35% increase indicating a good response to MSCT.Conclusion This study concludes that TMP is a potential biomarker that can predict the efficacy of MSCT in treating SLE, providing valuable insights for clinical practice and further research.